Forest use types of mammals in the Pasoh Forest Reserve and adjacent forest fragments - Md Noor, Nur Supardi; Hashim, Mazlan; Quah, Eng Seng; Numata, Shinya; Yasuda, Masatoshi; Nishimura, Sen; Yoshida, Keiichiro; Okuda, Toshinori (National Institute for Environmental Studies, Japan, 2005)
This study reports the works conducted in Pasoh Forest Reserve for determining how forest mammals use different forest types. Study have focused on the entire forest reserve which includes primary and secondary forest patches, and secondary forest fragments around agricultural fields, pastures, clearcuts, silviculture plantations, and residential areas. Samples were obtained from camera-trappings at selected locations in the forest reserve and adjacent fragment forests to reveal actual species composition of mammals in different forest types. Invasion of domestic animals and poaching are found remains high in the reserve.